Pengaruh Kualitas Makanan Terhadap Keputusan Pembelian di Sego Pedas Basman Cabang UNSIKA - Nestiti, Intan Liani; Elin, Elin; Yusuf, Abdul (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This research was conducted to test and analyze the influence of food quality on purchasing decisions at the Sego Pedas Basman Unsika branch, with food quality as variable X and buying decisions as variable Y. The method used in this research is a quantitative approach with simple linear regression analysis techniques. The sample in this study amounted to 106 respondents. After testing the hypothesis, the results showed that food quality significantly influenced purchasing decisions made by customers of Sego Pedas Basman, Unsika branch. However, it should be remembered that this research only examines the influence of food quality on purchasing decisions and not other factors that can influence purchasing decisions, such as service, price, and other factors. It is crucial to improve food quality further and meet customer expectations to maintain customer loyalty and, in turn, increase sales.